A town called Malice - Abramowitz, Adam (St. Martin's Press, 2019)
A bike messenger navigates Boston's gritty underworld of gangsters and blood money in this novel with more twists and turns than Boston's streets. Boston's baddest bike messenger Zesty Meyers is back in town...Bosstown. Zesty's life seems to be settling down after his last hospital visit and family secret reveal. But when his brother Zero starts acting oddly and pairs up with an unemployed Rabbi, Zesty knows something is awry. Then his father's old friend Klaussen turns up with stories from their run-ins with Boston's finest. His father's Alzheimer's has left Zesty and Zero with minimal knowledge of the past and rumors of the darkest of blood money. From shady bars to college campus underground poker leagues, Zesty's speeding towards trouble. Now Zesty must put his poker face on while he winds through the streets of Boston desperately trying to uncover his father's memory before Klaussen and his past catch up with him.